Normative Analysis of Criminal Accountability for Transnational Organized Drug Smuggling through False Concealment at Yogyakarta International Airport - Divia Avril Yuniar; Anis Widyawati (Law Research Review Quarterly, 2026)
This study discusses the legal gap in determining criminal liability for Transnational Organized Crime (TOC) networks that use false concealment methods in smuggling liquid methamphetamine at Yogyakarta International Airport. The main problem lies in the limitations of Indonesian criminal law in reaching criminal liability not only for the direct perpetrators, but also for the entire syndicate structure, such as coordinators, facilitators, and financiers, because the method of concealment makes it difficult to prove. This study uses a normative juridical approach by analyzing the integration between the Narcotics Law (Law No. 35 of 2009) as lex specialis and the Criminal Code, specifically Articles 55 and 56, in determining collective criminal liability. The results show that the method of disguising narcotics in the form of consumer goods reveals normative and structural weaknesses in the current criminal liability system. As a scientific contribution, this study proposes an expanded model of criminal liability that integrates narcotics law, the doctrine of participation, and money laundering provisions to cover the entire TOC network. This study concludes that strengthening criminal liability for transnational narcotics crimes requires updating legal doctrines, strengthening international cooperation, and implementing additional legal provisionsto make law enforcement more effective and provide a deterrent effect.